2019
DOI: 10.1111/ijac.13307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different storage media on the microhardness and wear resistance of resin‐matrix ceramics

Abstract: This in vitro study evaluated the microhardness and two-body wear of various computer-assisted design and computer-assisted manufacturing (CAD/CAM) resin-matrix ceramic materials stored in different storage media. For each material (Paradigm MZ100, Lava Ultimate, Vita Enamic, and Cerasmart), 40 disk-shaped specimens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The alterations in temperature may lead to thermal stress and various modifications to dental hard tissues as well as the restorative materials as a result of different thermal expansion coefficients. Nelsen (22) reported that thermal characteristics of restorative materials could be examined by using thermocycling test method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The alterations in temperature may lead to thermal stress and various modifications to dental hard tissues as well as the restorative materials as a result of different thermal expansion coefficients. Nelsen (22) reported that thermal characteristics of restorative materials could be examined by using thermocycling test method.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was detected regarding interactions between wear and surface hardness for the materials (28). Dayan and Mumcu reported weak correlation between wear and microhardness of the restorative materials tested: Paradigm MZ100, 3M Espe, USA; Lava Ultimate, 3M Espe, USA; Vita Enamic, Vita Zahnfabric, Germany; Cerasmart, GC Corp., Japan (22). In the present study, supporting the results of Cao et al, (28) Dayan and Mumcu (22), no correlation was observed for composite block, hybrid block and resin composite groups (p≥0.05).…”
Section: A Relation Between Inorganic Filler Content and Hardness In Resin-based Composites (31)mentioning
confidence: 99%
See 2 more Smart Citations
“…These failures may present themselves in the form of bulk fracture or chipping. The previously published literature indicates that the mechanical properties, such as fracture strength, 12 fracture toughness, 12 and microhardness, 12,17 of polymer‐based CAD/CAM restorative materials are affected by aging. Furthermore, it was stated that the thickness of CAD/CAM restorations was also effective on the fracture against chewing forces.…”
Section: Introductionmentioning
confidence: 99%